Fanlight - Ghosh, Ayan (2023)
Stained glass works on the fanlight with a golden cross. A foliage motif paired with a blue band runs around the border. A fanlight is a semicircular or semi-elliptical-shaped window with glazing bars or tracery sets radiating like an open fan, hence its name. This fanlight is placed above the door on the entrance (west) to St. Thomas Church.